Indonesian Higher Degree Education in the VUCA Era: Pathway to a Hybrid University? (Universitas Terbuka, 2023)
The COVID-19 pandemic has become a significant disruption in managing higher education institutions in various parts of the world. UNESCO released information that stated that there are at least around 60 million students affected worldwide due to 429 universities that had to be temporarily closed. Indonesia is experiencing the same phenomenon. In March 2020, it was recorded that 8 million students and 300 thousand lecturers had to undergo the transformation and start implementing online learning. At least 98% of the 4,582 tertiary institutions in Indonesia have implemented online learning. The online learning policy is regulated in a Minister of Education and Culture Circular concerning Online Learning which was strengthened by the Joint Decree of the Four Ministers in 2020. Even though many universities in Indonesia have implemented learning transformation, the processes may show differences. This article discusses how Universitas Padjadjaran's policies and strategies respond to the learning transformation policy and the challenges and mitigation strategies in overseeing the process. As one of the PTNBH in Indonesia, Unpad has started to adopt e-learning since 2003. Partially, COVID-19 accelerated the e-learning process through the Decree of the Rector of Universitas Padjadjaran Number 1190/UN6.RKT/Kep/HK/2020 requires the entire learning process at various levels to be carried out online. In line with Unpad's efforts to achieve World Class University, the Chancellor of Unpad initiated the Hybrid university policy in 2021. The new direction of the Hybrid university policy still refers to the Unpad Strategic Plan (2020-2024) implemented through various hybrid university infrastructure development programs, the Learning Management System platform (LMS) development, HR capacity building, etc.